PENGARUH LIKUIDITAS, EFISIENSI DAN UKURAN BANK TERHADAP PROFITABILITAS PADA BANK UMUM DI BURSA EFEK INDONESIA - KATARINA AFRIANI MAHDALENA SIMBOLON; YULIADI . (LP2MTBM MAKARIOZ, 2020)
This study was conducted aiming to determine the effect of Liquidity, Efficiency and Bank Size on Profitability at CommercialBanks listed on the Indonesia Stock Exchange. The method used to determine the sample is the purpose sampling method,namely the method of collecting samples with certain criteria. The study population consisted of 11 banks listed on theIndonesia Stock Exchange. Secondary data is data used in this study in the form of financial statements for the period 2015to 2016. The analysis used is multiple linear regression analysis. Data analysis used Statistical Package for Social Sciences(SPSS) version 20. The normality test results showed that the data used in this study were normally distributed. Based onthe multicollinearity test, the autocorrelation test and the heterokedasticity test found no variables that deviated from theclassical assumptions. Partially, the T Test shows that the liquidity variable has a negative and significant effect onprofitability, the efficiency variable has a negative and significant effect on profitability, while the size of the bank has anegative and not significant effect on profitability. But the F Test results show that these variables have a significant effect onprofitability and this research is worthy of research.